Performance of polycapillary X‐ray optics for confocal energy‐dispersive small‐angle X‐ray scattering. (10th November 2013) - Sun, Tianxi; Peng, Song; Liu, Zhiguo; Sun, Weiyuan; Ma, Yongzhong; Ding, Xunliang
<x xml:space="preserve">Abstract</x> A confocal energy‐dispersive small‐angle X‐ray scattering (EDSAXS) setup based on polycapillary optics was designed. In this confocal EDSAXS setup, a polycapillary slightly focusing X‐ray lens (PSFXRL) and a polycapillary parallel X‐ray lens (PPXRL) with a long input focal distance were placed confocally in the excitation channel and detection channel, respectively. This confocal configuration was helpful in improving the signal‐to‐noise ratio of the EDSAXS. The high gain in power density of the PSFXRL and PPXRL decreased the power requirement of the X‐ray source for EDSAXS. The confocal EDSAXS technology could be used to perform nondestructive and in situ analysis of samples such as milk powder in its packaging.